2019
DOI: 10.1016/j.heliyon.2019.e01551
|View full text |Cite
|
Sign up to set email alerts
|

Primary teeth microhardness and lead (Pb) levels

Abstract: Objectives Lead (Pb) exposure is associated with dental caries. Whether Pb affects tooth microhardness, is unclear. Our objective was to assess whether Pb concentration is associated with microhardness. Methods Exfoliated primary teeth were collected from 46 volunteers. Teeth were sectioned, one half of each tooth was tested for enamel Knoop microhardness. The remaining half was digested and Pb measured using an inductively coupled plasma-mass spectrometer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Pb and Cd that enter the mouth through food are incorporated into hydroxyapatite crystals, leading to the development of hydroxyapatite crystal deposition disease (HADD), a disease of uncertain etiology characterized by deposition of hydroxyapatite crystals in the shoulder and other arthrosis [10]. They replace calcium ions in teeth, causing enamel hypoplasia and increased abrasion and even tooth loss [11,12]. Browar et al showed that Cd causes loss of alveolar bone in a rodent model of long-term Cd poisoning [13], and further found that higher Cd content in human mandibles is associated with poorer periodontal scores [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pb and Cd that enter the mouth through food are incorporated into hydroxyapatite crystals, leading to the development of hydroxyapatite crystal deposition disease (HADD), a disease of uncertain etiology characterized by deposition of hydroxyapatite crystals in the shoulder and other arthrosis [10]. They replace calcium ions in teeth, causing enamel hypoplasia and increased abrasion and even tooth loss [11,12]. Browar et al showed that Cd causes loss of alveolar bone in a rodent model of long-term Cd poisoning [13], and further found that higher Cd content in human mandibles is associated with poorer periodontal scores [14].…”
Section: Introductionmentioning
confidence: 99%